Adolescent Girl's Knowledge And Practices Towards Menstrual Hygiene - mulani, Afsana; Shinde, Mahadeo; Katti, A.V. (International Journal of Psychosocial Rehabilitation, 2020)
Adolescence in young ladies has been perceived as a fierce period which implies the change from girlhood to womanhood and considered as a land characteristic of female puberty.This transitional period is separate with the start of "menarche '' which is usually recognized by little youths as a sign of improvement.AIM: To improve knowledge and practices regarding menstrual hygiene among adolescent girls.Objectives: To assess existing knowledge level regarding menstrual hygiene and effectiveness of educational program on knowledge, practices towards menstrual hygiene. To determine association with pre-test knowledge and practices towards menstrual hygiene of adolescent girls with demographic variables.Methods-A Study was done among 100 adolescent girls were selected from secondary school using Convenient Sampling method. The information was gathered utilizing pre tried self controlled survey recurrence circulation examination was performed. MAJOR FINDINGS Knowledge score regarding menstrual hygiene of adolescent girls before and after health teaching of 100 observations with pre-test mean of (4.11) and post-test mean of (7.61). The pre-test standard deviation was (1.569) and post-test (1.109). The computed‘t’ test statistical value is 16.686 since the ‘p’ value for the test is